Study of hydrodynamics interaction between ship to ship - Chen, Yih Lin (2019)
With increase of trading between nations coupled with low crude oil prices in recent years. Ship to ship transfer is on the rise. But this operation is dangerous as accident might happen which result in damaged ship hull, human safety and also cause environment pollution. Hydrodynamics of two ships in parallel are looked into in this report. Hydrodynamic forces are computed using computer simulation software. Wave diffraction problem is analysed for both of the ships in stationary state. Mooring lines tension and force and ship structure force excited by the wave are simulated. Tension on the mooring are also looked into with two conditions, mooring line unbreakable and mooring line breaking exceeding a specified tension. Results also showed that when the mooring line broke, ship structure force in the global Y direction has different result when compared with ship structure force in global Y direction before mooring line break.